2010
DOI: 10.1510/icvts.2009.214551
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of red blood cells: the impact on short-term and long-term survival after coronary artery bypass grafting, a ten-year follow-up

Abstract: Transfusion of red blood cells (RBC) and other blood products in patients undergoing coronary artery bypass grafting (CABG) is associated with increased mortality and morbidity. We retrospectively analyzed data of patients who underwent an isolated coronary bypass graft operation between January 1998 and December 2007. Mean follow-up was 1696+/-1026 days, with exclusion of 122 patients lost to follow-up and 80 patients who received 10 units of RBC. Of the remaining patients, 8001 (76.7%) received no RBC, 1621 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 15 publications
5
53
1
3
Order By: Relevance
“…Increased blood glucose is more associated with CCABG than beating heart coronary revascularization (37). Blood transfusion has been introduced as an operation outcome reducer (38). Studies show that blood transfusion is higher in on-pump patients (39), we have similar results.…”
Section: Discussionsupporting
confidence: 67%
“…Increased blood glucose is more associated with CCABG than beating heart coronary revascularization (37). Blood transfusion has been introduced as an operation outcome reducer (38). Studies show that blood transfusion is higher in on-pump patients (39), we have similar results.…”
Section: Discussionsupporting
confidence: 67%
“…1029 -1032 A prospective observational study of 8004 patients demonstrated that the transfusion of allogeneic red blood cells in CABG patients was associated with an increased risk of low-output heart failure irrespective of the extent of hemodilutional anemia. 1030 An adverse outcome may be caused by immunomodulation (known to occur with red blood cell transfusion), initiation of a systemic inflammatory response and its associated direct negative myocardial effects, reduced red blood cell capacity for adequate oxygen delivery 1031,1032 (diphosphoglycerate function in "banked" blood may cause tissue hypoxia), and changes in red blood cell morphology of transfused blood. Regardless of etiology, myocardial depression is observed consistently after allogeneic red blood cell transfusion, and this effect appears to be dose dependent.…”
Section: Transfusion: Recommendationmentioning
confidence: 99%
“…According to the study conducted by van Straten et al [21], the number of units transfused may be a predictor of early mortality (up to 30 days in the postoperative period), but not of late mortality. Comparing the expected survival, the authors concluded that in patients who received three or more units of RBC, the survival rate drops significantly when compared to patients who did not receive hemoderivative products.…”
Section: Discussionmentioning
confidence: 99%
“…Blood transfusion can also initiate a secondary inflammatory response by modifying the systemic inflammatory response of the patients and the direct introduction of bioactive substances into circulation, in addition to the primary inflammatory response initiated by the extracorporeal circulation [21][22][23].…”
Section: Discussionmentioning
confidence: 99%